Inovasi Pembuatan Hand Sanitizer Berbasis Ekstrak Daun Sirih dan Jeruk Nipis sebagai Alternatif Alami yang Efektif dan Ramah Lingkungan - Ahmad Muharrom; Angga Faisal Rahman; Dania Puri Azzahra; Syah Kumbara Lazuardi; Syiti Zahra Nur Zainab (Jurnal Pengabdian Cendekia, 2026)
The COVID-19 pandemic heightened hand sanitizer demand, yet chemical alcohol-based products often cause skin irritation and environmental pollution. This study aimed to develop natural hand sanitizer from betel leaf (Piper betle L.) and lime (Citrus aurantifolia) extracts via Community Service Program (PKM) in Dangdang Village, Cisauk. Employing applied-descriptive action research with mixed-methods, it targeted PKK mothers population (n=50) and purposive sample of 25-30 participants. Instruments included guidebooks, questionnaires, observations, and simple efficacy tests; data analysis used triangulation and descriptive statistics. Results revealed training successfully enhanced independent production knowledge, with 90% participant satisfaction on ease, antiseptic quality, and affordability. Conclusions affirm this innovation empowers local resources for sustainable hygiene solutions, recommending replication and advanced testing.